A implantação da Vulcabrás Azaleia no município de Frei Paulo/SE : impactos no desenvolvimento local - Matos, Paulo Rege Santos (2012)
The regional and local development in many Brazilian cities and especially in the Northeast from the 1990s, was based on tax incentives that did not take into account the aspects of identity and culture with the potential of these places, with the argument of persuasion generation employment and income for localities more humble. Given this scenario was implemented in the 2000s in the municipality of Frei Paulo (SE) the footwear industry "Vulcabrás Azaleia", which generates significant direct jobs and contributes substantially to socioeconomic changes of the city, but out of sync with the prevailing theme of local development and also to sustainable development. Thus this paper aims to examine sustainability from the perspective of local development in the municipality of Frei Paulo (SE) checking the proportionate influences from the footwear industry. This is an investigation of descriptive and explanatory character of quantitative and qualitative nature, data were collected by means of semi-structured questionnaire with open and closed questions, applied to the actors involved in the municipal context. The study concluded that there was job creation and which substantially increased the purchasing power of the population and therefore GDP growth of the city with a better distribution of income to the population through the HDI. Finally it is shown that the actors involved in the county in its entirety unaware of environmental responsibility actions performed by the footwear industry in favor of the locality, but also understand little or nothing of the issues involving sustainable development and local development